A Comparative Study on Human Trafficking as a Crime in South Africa - Ramsamooj, Jenine (Southern African Public Law)
With millions of people trapped in modern-day slavery, human trafficking is largely misunderstood, owing to limited data and research. Present-day human trafficking trends are linked to issues such as corruption, funding, public awareness, and poor anti-trafficking coordination. Over centuries, human trafficking has taken on a variety of forms ranging from enslavement in all its forms to organ removal. South Africa’s most significant achievement in combatting human trafficking is its own anti-trafficking legislation, namely the Prevention and Combatting of Trafficking in Persons Act of 2013. However, some provisions of this Act remain ineffective, thus impeding the fight against trafficking in the country. This article focuses on South Africa’s trafficking trends and anti-trafficking responses. It also highlights the hindrances obstructing the effective enforcement of its legislation by comparison to the first-world country Canada, to gain an understanding of effective anti-trafficking administration and execution to ultimately provide recommendations for South Africa to follow. For example, years before South Africa, Canada had already responded to international pressures regarding its anti-trafficking efforts. The country focused ample resources and funding on its anti-trafficking task team while South Africa followed a piecemeal approach in addressing human trafficking. This stems from a misunderstanding of the crime and policy frameworks, and mismanagement of funds. This article proposes that the South African government should strengthen its anti-trafficking measures by making funds easily accessible to victims and educating front-line responders to communicate effectively with victims.